Influence of discriminating factors of mental illness on the social wellbeing of patients in contemporary Nigerian society (2023)
Discrimination against individuals with mental illnesses is widespread and can have severe consequences for their recovery and well-being. In order to effectively address this issue, it is important to recognize, anticipate, and safeguard the rights of patients. A study was conducted in Ibadan to examine the social well-being of relatives of mentally ill patients and identify the distinguishing characteristics of mental illness. The research employed a descriptive methodology and utilized a simple random sampling technique, selecting 156 participants who completed a self-developed questionnaire. The collected data was analyzed using the Pearson Moment Correlation Coefficient. The findings revealed several significant relationships: knowledge was positively correlated with the social well-being of relatives (r = .182, n = 146, p < .05); attitude was also positively correlated (r = .0521, n = 146, p > .05); and behaviour showed a significant correlation as well. Based on these findings, it is recommended to enhance mental health literacy, as it can greatly benefit individuals and the overall population. Social workers should organize public awareness campaigns to educate the general public about the stigma associated with mental illness. Additionally, the government should prioritize mental health in budget allocations and allocate sufficient funding to support this area